Analysis of Red Cell Distribution Width and Carcinoembryonic Antigen As Predictor of Severity Colorectal Cancer - Eka Widia Pusfitasyari; Uleng Bahrun; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
The incidence of CRC is 16.5 cases in 100,000 population with 6.7% mortality of all malignancies. RDW-CV values and CEA levelswere used as predictors of severity in various malignancies. This study aimed to analyze the RDW-CV and CEA levels as predictors of CRC severity. A Retrospective study using medical record data of 245 CRC patients at Dr. Wahidin Sudirohusodo Hospital. Samples were grouped based on stage (metastatic and non-metastatic), tumor location (right colon, left colon, and rectum), type of care (outpatient and inpatient), and outcome (improved and died). The distribution of RDW-CV and CEA data was tested using the Kolmogorov-Smirnov test, comparison of stage, outcome, and type of care using the Mann-Whitney test, correlation with Spearman's correlation test, comparison by location using the Kruskal-Wallis test and ROC curve to determine the cut-off. The median age of subjects was 53.7±12.4 years. RDW-CV values and CEA levels were higher in the metastatic stage than non-metastatic (p=0.005 vs. p=0.000). There was a significant relationship between the incidence of metastases with RDW-CV (p=0.005) and CEA (p=0.000) in CRC. ROC curve analysis shows the optimal cut-off value for RDW-CV as a metastatic prediction is 14.35% (sensitivity 60.4%; specificity=50%), and CEA was 3.24 ng/mL (sensitivity 70.3%; specificity=52.1%).  RDW-CV value was highest in the right colon compared to the left colon and rectum (p=0.009). RDW-CV values and CEA levels were higher in patients with mortality than those who recovered (p=0.016 vs. p=0.055). This study shows a significant relationship between RDW-CV and CEA with the metastatic stage of CRC, and based on the outcome, RDW-CV was higher in the mortality group.